Analisis Kinerja Keuangan Daerah dan Pengaruhnya Terhadap Tingkat Kesejahteraan di Provinsi Jambi - Riskiya Indah Purnamasari Lubis (Universitas Batanghari Jambi, 2020)
The purpose of this study was to analyze regional financial performance and its influence on the level of public welfare and find out which variable are dominans on the level of publiv welfare. The research method use in this research is quantitative descriptive using secondary data. Types and sources of data used are secondary data collection. The data used in the study were obtained from relevant agencies. The analytical tool used in this study is the analysis of regional financial ratios and multiple linear regression analysis. The data analyzed are the ratio of regional independence and the ratio of effectiveness of PAD and minimum wage data in the last ten years namely 2009-2018. Based on simultaneous testing (Test F) note F count (1.557) is smaller than F table (4.74), this means that simultaneously there is no significant relationship between the independent variables (Independence Ratio and Effectiveness Ratio) to the dependent variable (Minimum Wages). For partial testing (t test) the conclusion is that the calculated value of t is smaller than t table in the variable independence ratio (-0.554 < 2.3646) and the Effectiveness ratio variable t value is smaller than t table of (-0.901 < 2.36346). The conclusion obtained in testing the analysis of regional financial ratios is the independence Ratio in the medium criteria which is not entirely dependent on the central government and the Effectiveness ratio in the criteria is very effective. While the results of the multiple linear regression analysis test that is the independence ratio and the effectiveness ratio has no effect on the Minimum Wages in Jambi Province.